How Does Social Interaction Affect Pro-Environmental Behaviors in China? The Mediation Role of Conformity - Zhu, Yuxin; Wang, Yin; Liu, Ziming (Frontiers in Environmental Science, 2021)
Environmental problems rooted in human behaviors have been the major obstacles to sustainable development in many countries. The promotion of residents’ pro-environmental behaviors may serve to mitigate environmental problems. In this paper, we understand residents’ pro-environmental behaviors from the perspective of social interaction. We distinguish between low-cost and high-cost pro-environmental behaviors and analyze to what extent social interaction may affect the two types of pro-environmental behaviors and whether conformity plays a mediation role, using the Chinese General Social Survey in 2013. We find that frequent social interaction increases residents’ low-cost pro-environmental behaviors but decreases residents’ high-cost pro-environmental behaviors. Conformity has no mediation role for low-cost pro-environmental behaviors but has a full mediation role for high-cost pro-environmental behaviors. We conclude that residents have a strong tendency to conform to the behavioral patterns of the social majority when such conformity can save their time, effort, or financial cost. To promote residents’ pro-environmental behaviors, their enforcement cost for the residents should be taken into account and adaptive policy instruments should be developed for different types of pro-environmental behaviors.